2018
DOI: 10.3389/fped.2018.00349
|View full text |Cite
|
Sign up to set email alerts
|

Low Sensitivity of Abbreviated Tilt Table Testing for Diagnosing Postural Tachycardia Syndrome in Adults With ME/CFS

Abstract: Introduction: Orthostatic intolerance is common among individuals with myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS). In some ME/CFS case definitions, orthostatic intolerance is considered a core feature of the disorder. Some studies have employed tilt table tests lasting 2–5 min to diagnose one common form of orthostatic intolerance, postural tachycardia syndrome (POTS). We examined the diagnostic yield of abbreviated durations of tilt testing in adults meeting criteria for ME/CFS, and identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This is important because physicians generally do 1-3 min of standing in a routine orthostatic assessment. Van Campen et al have shown that abbreviated Tilt Table testing of only 2-5 min misses a substantial proportion of those ultimately diagnosed with POTS during a 10-min Tilt Table test [13]. Plash et al compared Tilt Test versus Standing hemodynamics in POTS and state that while Tilt Testing produced larger increases in heart rate, both Tilt and Stand tests done for 10 min provide meaningful data [14].…”
Section: Discussionmentioning
confidence: 99%
“…This is important because physicians generally do 1-3 min of standing in a routine orthostatic assessment. Van Campen et al have shown that abbreviated Tilt Table testing of only 2-5 min misses a substantial proportion of those ultimately diagnosed with POTS during a 10-min Tilt Table test [13]. Plash et al compared Tilt Test versus Standing hemodynamics in POTS and state that while Tilt Testing produced larger increases in heart rate, both Tilt and Stand tests done for 10 min provide meaningful data [14].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, decreased oxygen extraction in a subset of PwME [7] suggests ME involves a problem of oxygen utilization rather than bioavailability. This phenomenon may be responsible for observed maladaptation in autonomic function, including orthostatic [8] and chronotropic intolerances [9].…”
mentioning
confidence: 99%